Modelling Strategy and Net Employment Effects of Renewable Energy and Energy Efficiency: A Meta-Regression - Spyridon Stavropoulos; Martijn J. Burger (Tinbergen Institute, 2019)
By conducting a meta-analysis of the empirical literature on the net employment effects of renewable energy, we explore the extent to which the reported net employment effects are driven by the applied methodology. We find that the reported conclusions on net employment effects are to a large extent driven by the methodology that is applied, where computable general equilibrium (CGE) and I/O methods that include induced effects and studies that consider only the near future in their study period (up to 2020) are generally less optimistic about net employment creation in the wake of the energy transition. In addition, we found that policy reports have a greater tendency to report a positive net employment effect than academic studies.
Keywords: J21; P18; Q42; 330; renewable energy; net employment; meta-analysis; circular economy